Assessing Passport Service Quality in the Digital Era: User Perceptions of the M-Paspor Application at the Class I Immigration Office TPI Jambi - Try Syeftiani; Muhammad Haris Saputra; Kurnia Permana (International Journal of Business and Quality Research, 2025)
This article discusses the digital transformation of passport services as part of public service reform in the immigration sector. The study analyzes public perceptions of the quality of M-Paspor–based passport services at the Class I Immigration Office TPI Jambi by integrating the SERVQUAL and e-service quality perspectives. The findings demonstrate that the implementation of digital-based passport services has been perceived very positively by service users, particularly in terms of accessibility, procedural certainty, and service efficiency. The consistency of high scores across service quality dimensions reflects the successful integration of digital systems with conventional service mechanisms. However, the analysis also reveals that the empathy dimension remains relatively weaker, indicating the need to strengthen human interaction and user experience within digital public services. Overall, this study confirms that digital transformation has contributed to improving passport service quality, while emphasizing that sustainable public value creation requires a balanced approach between technological innovation and user-oriented service delivery. The results provide empirical insights for strengthening digital public service governance in the immigration sector Key words: Passport Service Quality, Digital Transformation, SERVQUAL